FILM DAN IDEOLOGI POTRET ISLAM DALAM FILM-FILM HOLLYWOOD - Herry Hermawan (Universitas Prof. Dr. Moestopo (Beragama), 2018)
This research is concerned with Hollywoods portrayal of Islam. This research paper is basically analyses of four Hollywood Movies (Batman v Superman: Dawn of Justice; Avatar: The Last Airbender; Robocop 2014 and Iron Man 3). It consists the analysis of these movies to find out how Hollywood portrays Muslims, especially after 9/11. Through the qualitative research method the analysis techniques in use were genre and semiotics analysis. I analyzed and criticized the four movies scenes with regard to the language they used, the places where the scenes of movies took place and other minor details such as how the directors narrated and articulated different events and scenes with different Islamic symbols. The findings indicate that Islam and Muslims received negative coverage. A consistent stereotyped association with violence, terrorism, fundamentalism and extremism marks the representations of Islam and Muslims in Hollywood movies. These representations encapsulate the perception of Islam and Muslims by mass media to the point it becomes very difficult to perceive Islam and Muslims differently.